Peatland vascular plant functional types affect methane dynamics by altering microbial community structure. (11th May 2015) - Robroek, Bjorn J. M.; Jassey, Vincent E. J.; Kox, Martine A. R.; Berendsen, Roeland L.; Mills, Robert T. E.; Cécillon, Lauric; Puissant, Jérémy; Meima‐Franke, Marion; Bakker, Peter A. H. M.; Bodelier, Paul L. E.; Wurzburger, Nina
Summary Peatlands are natural sources of atmospheric methane (CH4), an important greenhouse gas. It is established that peatland methane dynamics are controlled by both biotic and abiotic conditions, yet the interactive effect of these drivers is less studied and consequently poorly understood. Climate change affects the distribution of vascular plant functional types (PFTs) in peatlands. By removing specific PFTs, we assessed their effects on peat organic matter chemistry, microbial community composition and on potential methane production (PMP) and oxidation (PMO) in two microhabitats (lawns and hummocks). Whilst PFT removal only marginally altered the peat organic matter chemistry, we observed considerable changes in microbial community structure. This resulted in altered PMP and PMO. PMP was slightly lower when graminoids were removed, whilst PMO was highest in the absence of both vascular PFTs (graminoids and ericoids), but only in the hummocks. Path analyses demonstrate that different plant–soil interactions drive PMP and PMO in peatlands and that changes in biotic and abiotic factors can have auto‐amplifying effects on current CH4 dynamics. Synthesis. Changing environmental conditions will, both directly and indirectly, affect peatland processes, causing unforeseen changes in CH4 dynamics. The resilience of peatland CH4 dynamics to environmental change therefore depends on the interaction between plant community composition and microbial communities.